Penegakan Peraturan Kepala Daerah Terhadap Pemilik Ternak yang Berkeliaran di Kecamatan Mamuju Kabupaten Mamuju Provinsi Sulawesi Barat - Mu'tamirudin Mu'tamirudin; Muhammad Fachrun Darmawan (Syntax Literate, 2023)
The problem of cattle (cows) roaming around has been going on for a long time in Mamuju District. The impact of this problem is a disturbance of peace and public order in society, for example housing and highways. Responding to this problem, the Mamuju Regency Government issued Regent Regulation Number 21 of 2021 concerning Amendments to Regent Regulation Number 34 of 2018 concerning Control of Livestock which it is hoped that this problem can be resolved. This study aims to see how the Enforcement of Regional Head Regulations concerning the Control of Livestock, the inhibiting factors and efforts to overcome these inhibiting factors. The research method used is a qualitative method with a case study approach. Data collection techniques used were participant observation, direct observation, interviews, documentation, document archives, and physical devices. The results of this study indicate that Regent Regulation Number 21 of 2021 concerning Amendments to Regent Regulation Number 34 of 2018 concerning Control of Livestock has not been running effectively and optimally. This can be seen based on the Law Enforcement theory by Soerjono Soekanto.